2018
DOI: 10.1007/s11678-018-0488-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment of olecranon fractures in the elderly—a systematic review

Abstract: Nonoperative treatment of olecranon fractures in the elderly-a systematic review Fractures of the olecranon represent a common elbow pathology and comprise around 1% of all fractures in the adult patient. The incidence of olecranon fractures is reported to be approximately 11.5/100,000/year. Most olecranon fractures are displaced fractures while up to 12% are stable undisplaced fractures [2, 11, 13, 14, 17]. Open reduction and internal fixation (ORIF) is considered the gold standard of treatment for olecranon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…A recent systematic review of four included studies described similar findings to the present study with a mean MEPI socre of 95, a mean DASH score of 12, a mean flexion of 133° (106-140°), a mean extension lag of 15° (0-30°) and a mean VAS score of 1 (0-8) [20]. The authors conclude that the available literature supports a consideration of nonoperative treatment in the low-demanding elderly patients [20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A recent systematic review of four included studies described similar findings to the present study with a mean MEPI socre of 95, a mean DASH score of 12, a mean flexion of 133° (106-140°), a mean extension lag of 15° (0-30°) and a mean VAS score of 1 (0-8) [20]. The authors conclude that the available literature supports a consideration of nonoperative treatment in the low-demanding elderly patients [20].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it cannot be answered if the surgical group would also be similarly satisfied or show similar good results if treated conservatively. Similar to other studies [20], there might have been a high risk of selection bias regarding the choice of treatment in our study, as younger patients were rather treated surgically and older ones conservatively. Up to date, no relevant conclusions can be drawn when comparing conservative treatment with surgical treatment, especially in regard to more active elderly patients and additional research with randomized controlled multicenter trials involving larger sample sizes and longer follow-ups are necessary [20].…”
Section: Discussionsupporting
confidence: 76%
“…A recent systematic review of nonoperative management of olecranon fractures demonstrated that reasonable clinical outcomes can be achieved with nonoperative treatment modalities in patients older than 70 years. 12 The authors concluded that nonoperative management should be considered in this cohort of patients. One of the 4 studies included demonstrated a mean MEPS of 95.3 in 22 fractures followed up for at least 6 months in patients older than 75 years.…”
Section: Discussionmentioning
confidence: 95%
“…With high complication rates in the use of tension band wiring, it remains unclear whether plate osteosynthesis would have a greater benefit, since only two patients received this procedure. Reviewing the existing studies regarding olecranon fractures highlights the need for RCTs in this field [18] .…”
Section: Olecranon Fracturesmentioning
confidence: 99%